A Population-Based Study on Injury Risk and Disparities Among Children With ADHD. Issue 8 (June 2023) - Shen, Jiabin; Shi, Junxin; Gauthier, Lynne; Li, Wenjun
Objective: Impaired attention and inhibitory control put children with ADHD at potentially high risk of injury—one of the leading causes of disability in the general pediatric population. Existing research has yet to examine this important health risk using nationally representative samples. This population-based study aimed to address this gap. Methods: National estimates of injury occurrences were generated from 66, 236 children in the Medical Expenditures Panel Survey 2010–2019 datasets. Multiple logistic regression models further examined the impact of injury type, age, race/ethnicity, sex, parental education, income, marital and insurance status on injury prevalence. Results: Compared to children without ADHD, those with ADHD have significantly higher injury prevalence ( OR = 1.20, 95% CI [1.07, 1.33]) across injury types and most sociodemographic subgroups. Conclusions: Children with ADHD are more likely to experience injury. Future research should investigate mechanisms of injury disparities to inform future preventive efforts.